Monitoring the safety of influenza A/H1N1 pandemic and seasonal vaccines in Morocco - Amina Tebaa; Raja Benkirane; Loubna Alj; Imad Cherkaoui; Rachida Soulaymani-Bencheikh (SAGE Publishing, 2022)
Background: A vaccination campaign against pandemic influenza A/H1N1 was implemented in Morocco between November 2009 and April 2010. Overall, 705,883 subjects were vaccinated by Pandemrix , Arepanrix , and Panenza . The adverse events following immunization (AEFIs) data comparison was made with the 2014/2015 seasonal influenza vaccination campaign that was specifically investigated. Aim: To evaluate the safety of the 2009 pandemic influenza A/H1N1 vaccine and to compare it to that of 2014 seasonal influenza vaccine. Methods: During the pandemic vaccination campaign, the Morocco Pharmacovigilance Centre reinforced passive AEFI surveillance with an active and prospective monitoring programme of 1000 immunized people over 6 months at 10 randomly selected vaccination centres. For the 2014/2015 seasonal vaccination campaign, AEFI data were collected from spontaneous notifications. Results: Active monitoring of 2009 pandemic collected 771 AEFI reports, corresponding to an AEFI incidence rate of 77.1% with vaccination by either Pandemrix or Arepanrix vaccine in 95% of cases. Reported AEFI were most frequently local (37.7%), general (29.5%), and neurological reactions (20.3%). Most of the AEFI (95.5%) were observed during the first 48 hours after vaccination, and the remainder within 2 weeks. None of the reported AEFI were serious case. The highest rate of notification was documented for health professionals, followed by patients with diabetes or chronic respiratory diseases. Concerning passive surveillance, the AEFI notification rate was significantly higher for the 2009/2010 pandemic vaccine (3.1 vs 1.2 per 10,000). However, there was no significant difference between pandemic and seasonal vaccination with regards to the serious adverse events (SAE) notification rate (0.3 vs 0.2 per 10,000). Conclusion: Data analysis indicates that the vaccines used against 2009 pandemic influenza in Morocco have a satisfactory safety profile, similar to the seasonal influenza vaccine with the exception of local reactions as observed previously in other countries.